Approach to the clinical history. A guide. - Angel Julio Romero Cabrera; Juan de Dios Rivero; Francisco Olascoaga Pérez; Reinaldo Pino Blanco; Benigno Figueiras Ramos.; Luis Gustavo Del Sol (Medisur)
-